Teatime: tales & rhymes - The Metropolitan Museum of Art (The Metropolitan Museum of Art, 2004)
Tea parties as represented in art in the Metropolitan Museum of Art are accompanied by poetry and literature.
Keywords: Poetry -- Poetry